Importance of Basic Attributes in Innovation Environment - Efficiency Analysis in the EU28 - Prokop, Viktor; Stejskal, Jan; Hájek, Petr; Kotková Stříteská, Michaela (International Society of Science and Applied Technologies, 2019)
Nowadays, measuring efficiency within countries´ innovation environment seems to be incremental in the process of gaining competitive advantage. Therefore, this study is aimed to evaluate efficiency in patent creation within EU28 countries. We are using specialized tool for assessing the effectiveness, performance and productivity of comparable production units Data Envelopment Analysis and data from Eurostat. Moreover, we are analyzing countries´ efficiency according to their innovation performance measured by European Commissions´ European Innovation Scoreboard 2017. Results show that only 5 out of the 28 European countries are effectively using basic attributes of Innovation Environment (investment in science and research; human resources in science and technology; cooperation with external research and development firms). All of these countries belong to the group of Innovation Leaders. We also propose practical implications (for each country) on how to improve and how to change their inputs and outputs to become (more) efficient and provide information about countries that could be benchmark for less efficient countries.
Význam základních atributů inovačního prostředí - analýza efektivnosti v EU28
Keywords: Importance; Basic; Attributes; Innovation; Environment; Efficiency; Analysis; the; EU28; Význam; základních; atributů; inovačního; prostředí; analýza; efektivnosti; EU28